Cechy systemów fonologicznych muzyki i mowy z perspektywy ewolucyjnej - Podlipniak, Piotr (Investigationes Linguisticae, 2018)
This article presents the phonological systems of music and speech as two different Humboldt systems which evolved for different reasons. The mental and the intersubjective characteristics of both systems are presented, including the relations between music and speech and the respective conceptual mental representations. The main aim of this paper is to suggest that the phonological system of music evolved earlier than articulated speech. As a result, the phonological system of speech emerged as a connection between two existing mental mechanisms, one that enabled our ancestors to use the Humboldt system in the domain of vocal communication and another which allowed them to combine referential meaning with sound symbols.